Extra-linguistic elements in learning second language - Kamaruddin, Rohaidah; Rosli, Muhammad Nur Akmal; Tuan Abdul Hamid, Tuan Nur Aisyah; Hamzah, Nor Sahayu; Mohammed Salleh, Minah (Macrothink Institute, 2019)
Extra-linguistic is a situation beyond the boundaries of linguistics; however, it is a free pattern that can exist in any field of study. In the field of language studies, extra-linguistic elements are taken into consideration as they provide the information in relation with motivation, emotion, attitudes, personality, and so on that are proven in helping a student in grasping certain languages. In this paper, the researcher connected a few ancillaries and extra-linguistic elements in language learning which are essential in order to indicate how other language learners accept and are willing to learn languages other than the mother tongue. Each learner or instructor needs to acknowledge that learning second language requires more than reading, writing or speaking in the language they want to learn but also the extra efforts to make the learning of the second language more meaningful. Educators must take the existence of extra-linguistic in language learning seriously because the elements in it can help students learn any language easily. Extra-linguistic elements are crucial in achieving educational success. Students, teachers, parents, school and educational ministry should be more concerned in order to ensure students success.